Le capitalisme à l’âge global : les mutations en cours transcendent-elles les spécificités nationales ? - Cynthia Ghorra-Gobin; Martine Azuelos (Revue LISA)
Has accelerating globalisation led to a convergence of national varieties of capitalism toward a single, market-led, ‘Anglo-Saxon’ model in the past few decades? To answer this question, this paper begins by characterising the major stages in the development and representation of capitalism over time. It then focuses on the contemporary period, with particular emphasis on the impact of financialisation and the prevalence of transnational dynamics. It argues that while these shifts have deeply affected the trajectories of national varieties of capitalism, increasing the role of market mechanisms, institutional diversification has nevertheless intensified. It concludes that hybridisation, rather than convergence, of models appears to be the defining characteristic of capitalism in the global age.